A Constant Market Share Analysis of India's Export Performance. (May 2014) - Singh, Kulwinder
In the light of substantial improvement in export growth and changing internal and external economic environment, this article investigates the major sources of India's exports performance during the post-liberalization period (1991–2011) by using constant market share model. It is found that growth of India's exports found to be outstanding as it was remained well above the growth of world exports as well as export growth of the majority of the giant exporters except China during this period. The analysis reveals that export performance was mainly attributed to their competitive strengths in the global export market, however world demand for exports also proved as its important source. It is also emphasized that competiveness of India's export remained prone to high inconsistencies arising out of changing external environment. Consistently negative composition effect came out as the most disturbing aspect of India's export performance. On the other hand, market distribution has laid marginally positive impact on export performance. Given the export promotion outward orientation as strategy of development, inconsistent competitiveness and wrong specialization pattern of exports could adversely influence their performance in particular and also have wider implications for the external sector in general.